On the existence of an optimally failure tolerant 7R manipulator Jacobian - Maciejewski, Anthony A.; Roberts, Rodney G. (Zielona Góra: Uniwersytet Zielonogórski)
Kinematically redundant manipulators have been proposed for use in remote or hazardous environments due to their potential for tolerance to joint failures. This article defines a local measure of failure tolerance based on the worst-case dexterity following a locked joint failure.
Keywords: sterowanie; sterowanie-teoria; sztuczna inteligencja; matematyka stosowana; informatyka